The role of historically Black colleges and universities (HBCUs) in cultivating the next generation of social justice and public service‐oriented moral leaders during the racial reckoning and COVID‐19 pandemics. Issue 1 (20th January 2023) - Franklin, Robert; Younge, Sinead; Jensen, Kipton
Abstract: In the United States, college has often served as an incubator for social change agents in the form of student activism and participation in broader social movements. Historically Black colleges and university (HBCUs) have played a pivotal role in social justice movements since their inception with the most notable example being the central role of HBCUs in the Civil Rights Movement. The role of HBCUs in cultivating exemplary leaders provides invaluable examples and frameworks for tackling the dual pandemics of COVID‐19 and the latest racial reckoning. The purpose of this paper is to provide a case study of how an all‐male HBCU contributes to the development of moral leadership and how that tradition has evolved with the current dual pandemics. We provide a historical overview of Morehouse's leadership models and provide a case study from students currently enrolled at Morehouse College, the only all‐male, historically Black college in the United States. Student participants described how leadership has evolved from previous generations, the impact of social media, and what it means to be a moral leader and how the HBCU tradition, shapes leadership. Highlights: Moral leadership is a cornerstone of many historically Black colleges and universities. The dual pandemics of COVID‐19 and the racial reckoning fueled public service amongst students. In the United States, college has often served as an incubator for social change agents.